'When you're boxing you don't think so much': pugilism, transitional masculinities and criminal desistance among young Danish gang members. (2nd July 2016) - Deuchar, Ross; Søgaard, Thomas Friis; Kolind, Torsten; Thylstrup, Birgitte; Wells, Liam
ABSTRACT: This paper draws upon international research evidence that suggests a relationship between protest masculinity and the manifestation of violent crime among young males, and that criminal desistance may be linked to (inter-) subjective processes such as the reconstruction of masculine identity. The paper considers the potential that pugilism (the art and practice of boxing) may have on enabling young, disadvantaged minority male gang members to find avenues for alternative identity construction and to gain transitional experiences which trigger self-confessed desistance actions. Drawing upon an ethnographic study conducted in a boxing rehabilitation centre on the outskirts of Copenhagen, Denmark, the paper reports on data gleaned from participant observation and qualitative interviews with 22 ethnic minority young men. Findings suggest that the masculine context within the rehabilitation programme provided the young men with a safe space to perform broader versions of locally dominated views on masculinity and to reflect on their current situations and dilemmas. The young men were clearly in transition and their desistance journeys were characterized by hope and ambition but also disappointment and despair. In some cases it appeared that the young men's dogged attempts to desist from crime became a new way for them to 'do masculinity'. The authors draw upon the findings to make recommendations for policy, practice and research.